Does a Sense of Social Presence During Conversation Affect Student's Shared Memory? Evidence From SS-RIF Paradigm - Zhu, Lin; Zhang, Jinkun (Frontiers in Public Health, 2021)
People constantly talk to one another about the past, and in so doing, they recount certain details while remaining silent about others. Collaborative or conversational remembering plays an important role in establishing shared representations of the past (e.g., the 911 attacks, Covid-19). According to the socially shared retrieval-induced forgetting (SS-RIF) effect, a listener will forget about relevant but unpracticed information during communication, due to intentional or unintentional selective retrieval of data by the speaker. The SS-RIF paradigm has been applied to explain how collective memory is shaped within the context of conversation/discourse. This study sought to determine if SS-RIF occurred only during face-to-face communication, or whether shared memories could be developed through other types of conversation quite common in modern society. We also investigated whether a level of social interaction in the real-world presence of others is a necessary condition for inducing SS-RIF, and if listeners experience different degrees of SS-RIF due to different levels of perceived social presence. We observed the SS-RIF phenomenon in listeners both in real life and video; the degree of forgetting was the same for the two conditions. These results indicate that social presence may not be associated with SS-RIF. Public silence affects the formation of collective memory regardless of the face-to-face presence of others, and thus physical presence is not necessary to induce SS-RIF.